Changing patterns of morbidity and mortality and the challenge to health care delivery systems of the future - Stini, William A. (Array, 1990)
Life expectancies are increasing throughout the world. Even though birth ratesare also declining, the large young populations of developing countries will continue to grow well into the 21st century. With improved health care, a higher proportion of the world's population is surviving into old age. Selective survival has been seen to produce superior life expectancies for individuals of disadvantaged groups who live to advanced age in the United States. Selective survival may now be occurring in the developing countries. The result may be an unprecedented increase in the aged populations of these countries. The burden on health care delivery systems throughout the world will be a matter of major concern in the first half of the 21st century